2016
DOI: 10.1016/j.cjtee.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous ganglion cyst of the lunate: A case report

Abstract: Intraosseous ganglion cyst of the carpal bones represents a rare cause of wrist pain. We report a case of a 42 year-old, right-handed female, who presented with pain of the right wrist following a fall on the palm of the hand. Clinical study revealed a moderate swelling over the mid-section of the palmar face and pain through extreme ranges of motion of the wrist. Plain radiographs and CT-scan of the wrist have revealed an intraosseous ganglion cyst of the lunate bone. Curetting-filling by Kuhlman's vasculariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Intraosseous ganglia are rare and commonly located in the tibia, fibula, humerus, ulna, radius, carpal and tarsal bones, acetabulum, and scapular bone [ 1 , 8 11 ]. The pathophysiology of intraosseous ganglia remains unclear, but it has been suggested that mechanical stress or trauma, synovial herniation, mucoid degeneration, and intramedullary metaplasia of mesenchymal cells may be the main causes [ 1 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intraosseous ganglia are rare and commonly located in the tibia, fibula, humerus, ulna, radius, carpal and tarsal bones, acetabulum, and scapular bone [ 1 , 8 11 ]. The pathophysiology of intraosseous ganglia remains unclear, but it has been suggested that mechanical stress or trauma, synovial herniation, mucoid degeneration, and intramedullary metaplasia of mesenchymal cells may be the main causes [ 1 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intraosseous ganglia are rare and commonly located in the tibia, bula, humerus, ulna, radius, carpal and tarsal bones, acetabulum, and scapular bone (1,(8)(9)(10)(11). The pathophysiology of intraosseous ganglia remains unclear, but it has been suggested that mechanical stress or trauma, synovial herniation, mucoid degeneration, and intramedullary metaplasia of mesenchymal cells may be the main causes (1,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…37 Histologically, they are similar to the soft tissue ganglion cyst. 38 Two patients (1.3%) presented with an intraosseous ganglion cyst, and both were treated with curettage with allograft bone packing. The lesions were in the metacarpal of the thumb and in the proximal phalanx of the middle finger.…”
Section: Intraosseous Bone Cystmentioning
confidence: 99%